Allergen-Specific Immunotherapy Increases Plasma Gelsolin Levels. Issue 3 (May 2014) - Janciauskiene, Sabina; Olejnicka, Beata; Koczulla, Rembert; Cardell, Lars-Olaf; Welte, Tobias; Westin, Ulla
Background: It has been observed that patients with allergic asthma/rhinitis have increased apoptosis of peripheral blood cells. This study was designed to explore the idea that the markers of apoptosis may help predict the response of allergen immunotherapy. Methods: The Allergy Department of University Hospital, Malmö, Sweden, recruited a total of 58 young adults (<35 years) with a history of birch pollen/grass pollen–induced allergic rhinitis. Their diagnoses were verified by positive skin-prick tests and the presence of serum-specific immunoglobulin E antibodies toward birch and/or grass pollen. Plasma samples were obtained from 34 patients before the start of immunotherapy and 24 patients after treatment. The control group consisted of 38 nonallergic individuals. The levels of plasma gelsolin, soluble forms of Fas (sFas) and Fas ligand (Fas-L), the chemokine CCL17 (thymus- and activation-regulated chemokine), and tissue inhibitor of metalloprotease (TIMP) 1, were measured by enzyme-linked immunosorbent assay. Results: In patients receiving immunotherapy plasma gelsolin levels were higher relative to those without immunotherapy (the median level was 23.97 μg/mL [range, 18–35.8 μg/mL] versus 21.2 μg/mL [range, 13.9–29.8 μg/mL]; p = 0.012) and were similar to those of healthy controls (24.7 μg/mL [range, 17.4–35.3 μg/mL]). Plasma levels of sFas, Fas-L, CCL17, and TIMP-1 did not differ between study groups. Only in controls did the plasma gelsolin levels inversely correlate to the levels of soluble Fas. Conclusion: Allergen-specific immunotherapy increases plasma levels of gelsolin, an antioxidant and antiapoptotic protein.